Budgets as Dynamic Gatekeepers - Pollack, Harold; Zeckhauser, Richard (Management Science, 1996)
Most large organizations allocate resources by means of fixed budgets: each subunit is normally entitled to spend a defined amount over a fixed period, usually one year. Fixed budgets create clear incentives for subunits to control costs. Yet such arrangements create major incentives for dynamic inefficiency, for example by encouraging subunits to exhaust their budgets toward the end of the fiscal year. This paper develops a dynamic optimization model to examine the incentives fostered by budget systems. It invokes the metaphor of physicians involved in a health care delivery system to examine incentives created by decentralized “gatekeeping” as a mechanism to control medical costs. The paper also discusses some methods to reduce the incentives for dynamic inefficiency that fixed budgets create.